Design Of Mini Generator Based On The Principle Of Water Flow Pressure By Using Vortex Turbine - Md Rozali, Sahazati; Mohd Nor, Rozilawati; Che Amran, Aliza; Mohamad Saleh, Saleha (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
In Malaysia, usually an electricity energy is generated based on fuel sources such as coal and natural gases. Since the consumption of electric energy is keep increasing yearly, the extinction of these sources becomes one of the main problems in this industry. Thus, the country needs to spend higher expenditure to import these sources since it has limited quantity and it is not a renewable energy source. In addition, the usage of the coal as sources affect the environment. Therefore, this research proposed a prototype of mini generator based on the principle of water flow pressure. The prototype is developed based on the flow of water vortex that is influenced by gravity and has the capability to generate energy at low-head flat geographically area. A controller for this system is designed by using Arduino. The objective of this research is to study the efficacy of this type of generator since it is one of the techniques to generate electricity. The efficiency of the designed prototype is analyzed based on different radius value of the basin and the effect of different type of motor used to spin the turbine. The results show that the smaller radius of the basin and direct drive motor generate higher voltage if the system is being tested individually. However, if both characteristics are combined together, the highest radius of basin with direct drive motor produced bigger value of voltage